Spectrum of Aerobic Microorganisms seen in Postoperative Wound Infections at Pakistan Institute of Medical Sciences (PIMS) Islamabad - Malik, Zafar Iqbal; Waqar, S H (International Journal of Pathology, 2018)
Background: Postoperative wound infection continues to be a major complication for patients undergoingoperative procedures, and remains a cause of concern for surgeons.Objective: The aim of this study was to determine spectrum of microorganisms in postoperativewound infections in general surgical wards at Pakistan Institute of Medical Sciences, Islamabad.Methodology: This prospective observational study was conducted by the Surgical Unit III, PIMS, Islamabad,from July 2012 to June 2014. Data of the patients developing postoperative wound infectionof various types were collected and analyzed. Data included clinical features, primary diagnosis, andtype of surgery performed, timing when evidence of wound infection was observed, the causative microorganism,and their antibiotic sensitivity pattern.Results: During the study period, 1621 patients were admitted to the surgical ward; out of which 1375underwent surgery. Among them, 136 patients developed wound infections, giving an overall woundinfection rate of 9.9%. In these patients, 129 pathogens were isolated from 121 positive culture samples.In 15 (11.0%) cases, no organism was grown. Majority of the wounds were infected with a single microbialorganism (113, 93.4%); while 8 samples (6.6 %) were infected with 2 different types of microbes.The most frequently isolated pathogen was E. Coli (grown in 43 cases, 33.3%); followed by MRSA(20.2%). The antibiotic sensitivity of various bacteria was studied, and it showed change in the sensitivitypattern of E. Coli.Conclusion: The E. coli is dominating organism in postoperative wound infection in general surgicalwards at our hospital. It is showing a change in susceptibility pattern. The problem of emerging drugresistance among bacteria can be minimized by adopting strict aseptic surgical procedures, judicial useof antibiotics, and proper wound care.Limitation of the study: Anarobic cultures were not performed